Gingerbread - Oyeyemi, Helen 1984- (Picador, 2018)
'A writer of sentences so elegant that they gleam' - Ali Smith Perdita Lee may appear your average British schoolgirl; Harriet Lee may seem just a working mother trying to penetrate the school social hierarchy; but there are signs that they might not be as normal as they think they are. For one thing, they share a gold-painted, seventh-floor flat with some surprisingly verbal vegetation. And then there's the gingerbread they make. Londoners may find themselves able to take or leave it, but it's very popular in Druhastrana, the far-away (and, according to Wikipedia, non-existent) land of Harriet Lee's early youth. In fact, the world's truest lover of the Lee family gingerbread is Harriet's charismatic childhood friend, Gretel Kercheval - a figure who seems to have had a hand in everything (good or bad) that has happened to Harriet since they met.Years later, when teenaged Perdita sets out to find her mother's long-lost friend, it prompts a new telling of Harriet's story, as well as a reunion or two. As the book follows the Lees through encounters with jealousy, ambition, family grudges, work, wealth, and real estate, gingerbread seems to be the one thing that reliably holds a constant value. Influenced by the mysterious place gingerbread holds in classic children's stories - equal parts wholesome and uncanny; from the tantalizing witch's house in Hansel and Gretel to the man-shaped confection who one day decides to run as fast as he can - beloved novelist Helen Oyeyemi invites readers into a delightful tale of a surprising family legacy, in which the inheritance is a recipe. Endlessly surprising and satisfying, written with Helen Oyeyemi's inimitable style and imagination, Gingerbread is a true feast for the reader